Bird Biodiversity of Pariyej Lake, Kheda, Gujarat: An Ecological Assessment (International Journal of Food and Nutritional Sciences, 2023)
Pariyej Lake, a man-made reservoir in Kheda District, Gujarat, serves as a critical wetland habitat supporting rich avian diversity. This study documents 167 bird species recorded between 2016–2018 through systematic